Preparation method of water-based high-temperature-resistant nano coating
By using the method of fusing acrylic matrix and additives in aqueous nano-temperature resistant coatings and adding specific absorbent C, the problems of large coating density and poor high-temperature resistance are solved, and the high-temperature resistance and corrosion resistance of the coating are achieved, which is suitable for high-temperature corrosion environments.
Patent Information
- Application Number
- CN202510064417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing aqueous nano high-temperature resistant coatings have problems in the coating with high density, poor high-temperature resistant characteristics, poor corrosion resistance, poor impedance matching, and narrow wave absorbing frequency band.
The acrylic matrix is fused with the additive to form a water-soluble emulsion, and the absorbent C is added, which comprises an absorbent connected to an acrylic resin, nano-preservative, nano-coal coated with organic-inorganic nanometal composite material and an oxide metal nanoparticle absorber. The aqueous nano-high temperature resistant coating is formed by high-speed mixing and stirring.
The coating has achieved high temperature resistance of 800-1500 degrees, improved high temperature pitting, stress corrosion and intergranular corrosion resistance, enhanced adhesion, corrosion resistance and hardness, and is suitable for large-scale industrial production, especially in high-temperature corrosion sites in steel plants and thermal power plants.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano coatings, in particular to a method for preparing a water-based high-temperature-resistant nano coating. Background Art
[0002] In recent years, with the enhancement of people's environmental awareness and the shortage of energy, the research, development and promotion of water-based coatings have received more and more attention from people, and the pollution and toxicity of fire-retardant coatings have also been paid more and more attention. The development of high-solid, water-based, solvent-free fire-retardant coatings, that is, non-toxic and low-pollution high-performance fire-retardant coatings has become an important research direction. In the development of water-based systems, on the one hand, water is used as a solvent and dispersion medium during the production and formulation process to reduce the content of volatile organic compounds (VOC); the main film-forming materials of the products are selected, and materials with good fire resistance, high physical and chemical properties, easy to obtain raw materials, and meet environmental protection requirements are selected. At present, most of them are prepared by filling refractory materials with organic resin as the bonding base material, which has the disadvantages of high density, poor high temperature resistance, poor corrosion resistance, poor impedance matching, and narrow absorption band. Therefore, in view of the above problems, a preparation method of water-based nano high temperature resistant nano coating is proposed. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a water-based nano-high temperature resistant nano-coating to solve the problems raised in the above background technology that the general water-based nano-high temperature resistant nano-coating has high density in the coating, poor high temperature resistance, poor corrosion resistance, poor impedance matching, and narrow absorption band.
[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a water-based nano-high temperature resistant nano-coating, comprising an acrylic matrix, an auxiliary agent and an absorbent C, wherein the acrylic matrix, the auxiliary agent and the absorbent are used to synthesize a nano-coating, and the acrylic matrix and the absorbent C are both water-soluble emulsions, and the acrylic matrix is used to prepare an acrylic resin, and the absorbent C comprises an absorbent connected to a nano-corrosion protection of acrylic resin, an organic-inorganic nano-metal composite material coated with an oxide metal nano-particle absorbing powder, and the acrylic matrix is an organic compound with a chemical formula of C3H4O2, containing a vinyl group and a carboxyl group, and the auxiliary agent is mixed into the acrylic matrix and the absorbent C.
[0005] Preferably, the organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are selected from one or more of chromium and molybdenum, and the organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are mixed into the absorbent C for preparation. The organic-inorganic nano-metal composite material is prepared by using resin, rubber, ceramic and metal matrix as continuous phase, nano-sized metal, semiconductor, rigid particles and other inorganic particles, fibers, nano-carbon tube modifiers as dispersed phase, and the modifier is uniformly dispersed in the matrix material.
[0006] Preferably, the absorbent C is obtained by the following method: acrylic resin is coated on the surface of nano-metal or nano-metal oxide powder, and it is absorbent A, polyisocyanate prepolymer is coated on the surface of absorbing alloy powder, and it is absorbent B, and the polyisocyanate includes diisocyanate, triisocyanate and their modified products.
[0007] Preferably, the absorbent A and the absorbent B are placed in a solvent, the hydroxyl groups on the surface of the absorbent A react with the NCO groups on the surface of the absorbent B, and the absorbent A and the absorbent B can be tightly connected together to form an absorbent C, and the mass ratio of the hydroxylated acrylic resin to the polyisocyanate prepolymer in the absorbent C is 90:(10-30), and the hydroxylated acrylic resin is prepared by polymerization reaction of acrylic acid and its derivatives with alcohol compounds (such as alkyd acid, hydroxylated acrylic acid).
[0008] Preferably, the nano coating comprises: component A and component B, wherein component A comprises the following raw materials in parts by weight: 80-100 parts of acrylic matrix, 10-30 parts of auxiliary materials, 40-60 parts of absorbent C, and component A contains nano chromium oxide, cobalt oxide and zirconium oxide, wherein component B comprises the following raw materials in parts by weight: 8-15 parts of curing agent, and component B contains silicon oxide and titanium oxide.
[0009] Preferably, a resin matrix is provided between the nano coating and the substrate, and the resin matrix bonds and fuses the nano coating and the substrate, and the resin matrix includes: one of epoxy resin, polyurethane resin, and silicone resin.
[0010] Preferably, the auxiliary agent is a solvent, a mixture in a weight ratio of (15-25):1, and the solvent is one of xylene, ethanol and butyl acetate.
[0011] Preferably, the auxiliary agent is mixed with the acrylic matrix to form a water-based acrylic emulsion, and the acrylic emulsion is highly fused, and the absorbent C is added to the acrylic emulsion.
[0012] Preferably, the method comprises the following steps:
[0013] Step 1: Mix the acrylic matrix and additives and stir thoroughly until they are completely dissolved;
[0014] Step 2: Add the weighed absorbent C to the mixed liquid obtained in step 1 while stirring, disperse at high speed, and after confirming that it is uniform and free of agglomeration, a usable nano coating is obtained.
[0015] Preferably, the stirring speed in step 1 and step 2 is 360 rpm to 600 rpm, and the stirring time is 5 min to 10 min.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: the acrylic matrix and the additive are fused with each other, and the additive is added to the water-soluble emulsion in which the acrylic matrix and the additive are melted to react, and after high-speed mixing and stirring, a water-based nano high-temperature resistant coating in the form of a water-soluble emulsion is finally formed. The water-based nano high-temperature resistant coating can withstand high temperatures of 800-1500 degrees, and solves high-temperature pitting, stress corrosion and intergranular corrosion caused by high temperatures. The water-based nano high-temperature resistant coating has good adhesion (0 level by the hundred grid method, greater than 12MPa by the drawing method), good corrosion resistance, and high hardness. It is suitable for industrial large-scale production, especially for use in high-temperature corrosion places such as steel mills and thermal power plants. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1
[0019] A water-based nano high temperature resistant nano coating comprises an acrylic matrix, an auxiliary agent and an absorbent C. The acrylic matrix, the auxiliary agent and the absorbent are used to synthesize the nano coating. Both the acrylic matrix and the absorbent C are water-soluble emulsions. Meanwhile, the acrylic matrix is used to prepare acrylic resin. The absorbent C comprises an absorbent connected with a nano anticorrosion of acrylic resin, an organic-inorganic nano metal composite material and an oxide metal nano particle absorbing powder.
[0020] Furthermore, the organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are made of chromium.
[0021] Furthermore, absorbent C is obtained by the following method: acrylic resin is coated on the surface of nano-metal or nano-metal oxide powder to obtain absorbent A, polyisocyanate prepolymer is coated on the surface of absorbing alloy powder to obtain absorbent B, absorbent A and absorbent B are placed in a solvent, hydroxyl groups on the surface of absorbent A react with NCO groups on the surface of absorbent B, and absorbent A and absorbent B can be tightly connected together to form absorbent C, and the mass ratio of hydroxyl acrylic resin to polyisocyanate prepolymer in absorbent C is 90:15.
[0022] Furthermore, the nano coating comprises: component A and component B, wherein component A comprises the following raw materials in parts by weight: 85 parts of acrylic matrix, 15 parts of auxiliary materials, 45 parts of absorbent C, and component A contains nano chromium oxide and zirconium oxide, wherein component B comprises the following raw materials in parts by weight: 10 parts of curing agent, and component B contains silicon oxide, a resin matrix is provided between the nano coating and the substrate, and the resin matrix bonds and fuses the nano coating and the substrate, and the resin matrix comprises: one of epoxy resin, polyurethane resin, and silicone resin.
[0023] Furthermore, the auxiliary agent is a solvent, a mixture of xylene, ethanol and butyl acetate in a weight ratio of 17:1, and the auxiliary agent is mixed with the acrylic matrix to form an aqueous acrylic emulsion, and the acrylic emulsion is highly fused, and absorbent C is added to the acrylic emulsion.
[0024] The acrylic matrix and the additive are mixed and stirred until completely dissolved, and then the weighed absorbent C is added to the mixture liquid of the acrylic matrix and the additive while maintaining stirring. After high-speed dispersion, a usable nano coating is obtained after confirming that it is uniform and has no agglomeration phenomenon. Stirring is performed at a speed of 400 rpm and a stirring time of 5 minutes. After mixing and stirring, the water-based nano high-temperature resistant coating can withstand high temperatures of 800-1500 degrees.
[0025] The prepared nano coating was combined with a resin matrix to conduct experiments on substrates. It was sprayed onto a 900×900mm substrate with a spraying thickness of 1mm. After the coating was cured, the substrate covered with the nano coating was cut into multiple pieces of 180×180mm on average. Six panels were randomly selected to test the high temperature resistance of the nano coating.
[0026] performance 1 2 3 4 5 6 Tensile Strength 20.8 18.9 19.5 20.5 19.2 19.7 Water absorption 83.5 79.6 80.8 85.6 81.1 83.4 High temperature resistance 2.4 2.8 3.2 2.7 3.1 3 Degradation peak 550 519 535 571 552 563
[0027] From the above data, it can be seen that the high temperature resistance of each small part of the coating is very small, which shows that the high temperature resistance is stable, the corrosion resistance is good, and the surface flatness is high.
[0028] Example 2
[0029] A water-based nano high temperature resistant nano coating comprises an acrylic matrix, an auxiliary agent and an absorbent C. The acrylic matrix, the auxiliary agent and the absorbent are used to synthesize the nano coating. Both the acrylic matrix and the absorbent C are water-soluble emulsions. Meanwhile, the acrylic matrix is used to prepare acrylic resin. The absorbent C comprises an absorbent connected with a nano anticorrosion of acrylic resin, an organic-inorganic nano metal composite material and an oxide metal nano particle absorbing powder.
[0030] Furthermore, the organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are made of molybdenum.
[0031] Furthermore, absorbent C is obtained by the following method: acrylic resin is coated on the surface of nano-metal or nano-metal oxide powder to obtain absorbent A, polyisocyanate prepolymer is coated on the surface of absorbing alloy powder to obtain absorbent B, absorbent A and absorbent B are placed in a solvent, hydroxyl groups on the surface of absorbent A react with NCO groups on the surface of absorbent B, and absorbent A and absorbent B can be tightly connected together to form absorbent C, and the mass ratio of hydroxyl acrylic resin to polyisocyanate prepolymer in absorbent C is 90:25.
[0032] Furthermore, the nano coating comprises: component A and component B, wherein component A comprises the following raw materials in parts by weight: 95 parts of acrylic matrix, 25 parts of auxiliary materials, 55 parts of absorbent C, and component A contains nano cobalt oxide and zirconium oxide, wherein component B comprises the following raw materials in parts by weight: 10 parts of curing agent, and component B contains titanium oxide, a resin matrix is provided between the nano coating and the substrate, and the resin matrix bonds and fuses the nano coating and the substrate, and the resin matrix comprises: one of epoxy resin, polyurethane resin, and silicone resin.
[0033] Furthermore, the auxiliary agent is a solvent, a mixture in a weight ratio of 23:1, and the solvent is one of xylene, ethanol, and butyl acetate. The auxiliary agent is mixed with the acrylic matrix to form an aqueous acrylic emulsion, and the acrylic emulsion is highly fused. At the same time, absorbent C is added to the acrylic emulsion.
[0034] The acrylic matrix and the additive are mixed and stirred until completely dissolved, and then the weighed absorbent C is added to the mixture liquid of the acrylic matrix and the additive while maintaining stirring. After high-speed dispersion, after confirming that it is uniform and has no agglomeration phenomenon, a usable nano coating is obtained. Stirring is performed at a speed of 550 rpm and a stirring time of 10 minutes. After mixing and stirring, the water-based nano high-temperature resistant coating can withstand high temperatures of 800-1500 degrees.
[0035] The prepared nano coating was combined with a resin matrix to conduct experiments on substrates. It was sprayed onto a 900×900mm substrate with a spraying thickness of 1mm. After the coating was cured, the substrate covered with the nano coating was cut into multiple pieces of 180×180mm on average. Six panels were randomly selected to test the high temperature resistance of the nano coating.
[0036] performance 1 2 3 4 5 6 Tensile Strength 21.8 21.9 22.5 23.5 22.2 21.7 Water absorption 85.5 82.3 84.1 85.6 84.9 82.9 High temperature resistance 3.7 3.6 3.5 3.4 3.1 3.9 Degradation peak 596 607 619 610 583 625
[0037] Example 3
[0038] A water-based nano-high temperature resistant nano-coating, in the coating preparation method: the coating is divided into two emulsion-type nano-materials and mixed with each other, and an auxiliary agent is added to promote the reaction. An acrylic matrix, auxiliary materials and absorbent C are prepared in one material, and the fused nano-material is water-soluble, and the other is a curing agent. The auxiliary agent is added when the acrylic matrix, auxiliary materials and absorbent C are stirred, and the mixed liquid is kept highly dispersed during the stirring process, and then the first one is formed under the action of the auxiliary agent, and the second one is stirred in the same manner, and finally the two nano-materials are fused according to proportion.
[0039] Then the coating was divided into six parts and coated on five substrate samples with the same surface environment. After the coating dried for 3 hours, the five substrate samples were placed in an oven and baked at 1000℃ for 24 hours. The surface coating of each group of metal samples was observed. The test results are shown in the table:
[0040]
[0041] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A water-based nano-high temperature resistant nano-coating, comprising an acrylic matrix, an additive and an absorbent C, characterized in that: The acrylic matrix, the auxiliary agent and the absorbent are used to synthesize the nano coating, and the acrylic matrix and the absorbent C are both water-soluble emulsions. The acrylic matrix is used to prepare acrylic resin. The absorbent C contains an absorbent connected with a nano anticorrosion of acrylic resin, an organic-inorganic nano metal composite material and an oxide metal nano particle absorbing powder. The acrylic matrix is an organic compound with a chemical formula of C3H4O2, which contains a vinyl group and a carboxyl group. The auxiliary agent is mixed into the acrylic matrix and the absorbent C.
2. The water-based high temperature resistant nano coating according to claim 1, characterized in that: The organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are selected from one or more of chromium and molybdenum, and the organic-inorganic nano-metal composite material and the metal oxide nano-particle absorbing powder are mixed into the absorbent C for preparation. The organic-inorganic nano-metal composite material is prepared by using resin, rubber, ceramic and metal matrix as continuous phase, nano-sized metal, semiconductor, rigid particles and other inorganic particles, fiber, nano-carbon tube modifier as dispersed phase, and the modifier is uniformly dispersed in the matrix material.
3. The water-based high temperature resistant nano coating according to claim 2, characterized in that: The absorbent C is obtained by the following method: coating the surface of nano metal or nano metal oxide powder with acrylic resin to obtain absorbent A, coating the surface of absorbing alloy powder with polyisocyanate prepolymer to obtain absorbent B, and the polyisocyanate includes diisocyanate, triisocyanate and their modified products.
4. The water-based high temperature resistant nano coating according to claim 3, characterized in that: The absorbent A and the absorbent B are placed in a solvent, the hydroxyl group on the surface of the absorbent A reacts with the NCO group on the surface of the absorbent B, and the absorbent A and the absorbent B can be tightly connected together to form an absorbent C. At the same time, the mass ratio of the hydroxyl acrylic resin to the polyisocyanate prepolymer in the absorbent C is 90:(10-30), and the hydroxyl acrylic resin is prepared by polymerization reaction of acrylic acid and its derivatives with alcohol compounds (such as alkyd acid, hydroxyl acrylic acid).
5. The water-based high temperature resistant nano coating according to claim 4, characterized in that: The nano coating comprises: component A and component B, wherein component A comprises the following raw materials in parts by weight: 80-100 parts of acrylic matrix, 10-30 parts of auxiliary materials, 40-60 parts of absorbent C, and component A contains nano chromium oxide, cobalt oxide and zirconium oxide, wherein component B comprises the following raw materials in parts by weight: 8-15 parts of curing agent, and component B contains silicon oxide and titanium oxide.
6. The water-based high temperature resistant nano coating according to claim 5, characterized in that: A resin matrix is arranged between the nano coating and the substrate, and the resin matrix bonds and fuses the nano coating and the substrate. The resin matrix comprises one of epoxy resin, polyurethane resin and silicone resin.
7. The water-based high temperature resistant nano coating according to claim 6, characterized in that: The auxiliary agent is a solvent, which is a mixture in a weight ratio of (15-25):1, and the solvent is one of xylene, ethanol and butyl acetate.
8. The water-based high temperature resistant nano coating according to claim 6, characterized in that: The auxiliary agent is mixed with the acrylic matrix to form a water-based acrylic emulsion, and the acrylic emulsion is highly fused. At the same time, the absorbent C is added into the acrylic emulsion.
9. The method for preparing a water-based high temperature resistant nano coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: Step 1: Mix the acrylic matrix and additives and stir thoroughly until they are completely dissolved; Step 2: Add the weighed absorbent C to the mixed liquid obtained in step 1 while stirring, disperse at high speed, and after confirming that it is uniform and free of agglomeration, a usable nano coating is obtained.
10. The method for preparing a water-based high temperature resistant nano coating according to claim 9, characterized in that: The stirring speed in step 1 and step 2 is 360 rpm to 600 rpm, and the stirring time is 5 min to 10 min.